2011
DOI: 10.5030/jcigsjournal.26.137
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Performance of Geosynthetic Clay Liners Used in Acid Rock Drainage Mitigation

Abstract: Longterm barrier performance of geosynthetic clay liners (GCLs) when exposed to acid rock drainage (ARD), which is one of the most severe and expensive environmental problems facing the mining and some construction operations, was evaluated. Free swelling, sorption, and a ninemonth hydraulic conductivity tests on a needle punched GCL against an artificial ARD (pH = 3) that contained Al, Fe, Cu, Zn, As, and Pb, were conducted. Free swelling tests showed that a high metal concentration and/or a low pH negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…However, the hydraulic conductivity of GCLs may change over time especially due to metal interaction or precipitation. Naka et al (2011) found that hydraulic conductivity of GCL permeated with ARD gradually increased over time, until around 150 PVF. After this point, it stabilized, reaching an average permeability value of 5.0×10 -10 m/s.…”
Section: Effects Of Permeation Timementioning
confidence: 99%
“…However, the hydraulic conductivity of GCLs may change over time especially due to metal interaction or precipitation. Naka et al (2011) found that hydraulic conductivity of GCL permeated with ARD gradually increased over time, until around 150 PVF. After this point, it stabilized, reaching an average permeability value of 5.0×10 -10 m/s.…”
Section: Effects Of Permeation Timementioning
confidence: 99%